Relation between the continuum threshold and the Polyakov loop with the QCD deconfinement transition - Carlomagno, Juan Pablo (2019)
Using vector and axial-vector correlators within finite-energy sum rules with inputs from a chiral quark model, coupled to the Polyakov loop, with nonlocal vector interactions, we extend our previous work to confirm the equivalence between the continuum threshold s0 and the trace of the Polyakov loop Φ as order parameters for the deconfinement transition at finite temperature T and quark chemical potential μ. The obtained results are in agreement with our initial conclusion, where we showed that s0(T,μ) and Φ(T,μ) provide the same information for the QCD deconfinement transition.